Ultrasound guided central venous cannulation in ICU: Retrospective analysis of a single center experience - Shrestha, Gentle S.; Shrestha, Manjit; Shrestha, Bibeka (Journal of Advances in Internal Medicine, 2020)
Background and Aims: Central venous cannulation is a common procedure in intensive care unit. Use of ultrasound guidance can decrease complications and increase successful cannulations.Methods: Patients who underwent ultrasound guided central venous cannulation over a duration of one year, in a single center, were analyzed retrospectively.Results: A total of 101 patients were analyzed. Internal jugular vein was cannulated in 84 (83.2%) and femoral vein was cannulated in 17 (16.8%) patients. Cannulation was successful in all cases. Elective cannulation was performed in 80 (79.2%) of patients and emergency cannulation was performed in 21 (20.8%) patients. Platelet count was less than 50000/cu mm in 30 (29.7%) patients and prothrombin time was more than 13 seconds in 84 (83.2%) patients. Cannulation was successfully performed in first attempt in 99 (98%) patients. None of the patients had arterial puncture, major bleeding, pneumothorax, arrhythmias or catheter malposition. One patient developed hematoma at the catheter insertion site.Conclusions: When performed by an experienced operator, ultrasound guidance can enhance safety and improve success for central venous cannulation.